Career development and turnover intention of health information management professionals in Ibadan Oyo State (Lead City International Journal of Library, Information & Communication Sciences, 2024)
Health information management (HIM) professionals are integral parts of the health service delivery structure. However, despite their strategic importance to the smooth flow of health information in hospitals, issues concerning HIM professionals are often relegated to the background. This often led to turnover intention which can disrupt the smooth operation of hospitals. As a result, this study examined the influence of career development on turnover intention of health information management professionals in Ibadan Oyo State. Descriptive survey research design was adopted for the study. A structured questionnaire was adopted as the instrument for data collection. The study population consist of one hundred and twenty-seven (127) health information management professionals in six government hospitals in Oyo State. Total enumeration was adopted due to the population size. The quantitative data collected was analysed using both descriptive and inferential statistics. The study found low levels of turnover intention (Mean =3.12), and high level of career development (Mean =3.30) among the respondents. The test of hypothesis also showed that career development has significant influence on turnover intention (R2= 0.345, p= 0.000) among the HIM professionals. The study concluded that the although the turnover intention is low, there are still underlying factors that must be addressed to ensure that HIM professional remain committed to their employers. It was therefore recommended that the low turnover reported in this study is maintain by focusing more on employee welfare and protecting the interest of the health information management.